Collaborative Strategy Integrating School Environment and Self-Efficacy for Strengthening Metacognitive Competence and Learning Independence - Yewang, Markus U. K.; Saragih, Fernando; Loe, Andri Paulus; Mau Manek, Alfridus; Butar-Butar, Agustina; Sasea, Tirtania (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2025)
This study examines the influence of the school environment on students’ independent learning, with self-efficacy and metacognitive skills functioning as sequential mediators among senior high school students in Malaka Regency. Employing an explanatory survey design, data were collected from Grade XI students across six purposively selected schools representing twelve districts. The structured questionnaire comprised 41 items measured on a 5-point Likert scale and assessed four constructs: school environment, self-efficacy, metacognitive skills, and independent learning. Data analysis was conducted using the PROCESS Macro (Model 6) in SPSS 23. The results indicate that the school environment has a significant effect on self-efficacy (β = 0.2137, p = 0.0017) and independent learning (β = 0.1794, p = 0.0066), whereas its influence on metacognitive skills is not significant (β = −0.0241, p = 0.7542). Additionally, self-efficacy does not significantly affect metacognitive skills (β = 0.1354, p = 0.0731) or independent learning (β = −0.0125, p = 0.8468). In contrast, metacognitive skills exert a significant positive influence on independent learning (β = 0.2365, p = 0.0001). The total effect of the school environment on independent learning remains significant (β = 0.1779, p = 0.0077), although the indirect effects through the mediating variables are not statistically significant. These findings suggest that a supportive and well-structured school environment directly enhances students’ independent learning more effectively than indirect psychological pathways. It is recommended that educational institutions further strengthen their learning environments and incorporate metacognitive skill development to promote students’ self-regulation and autonomy.